(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of antibiotic skin testing in patients with a history of allergy. Methods: A prospective, cross-sectional descriptive study was conducted in patients with a history of allergy who attended the Allergen Clinic of the Center for Allergy and Clinical Immunology from January to March 2025. Results: The study included 872 patients who underwent a total of 5,195 skin tests, comprising 4,875 skin prick tests (93.8%) and 320 intradermal tests (6.2%). Only 55 patients had positive skin test results to at least one antibiotic (44 skin prick tests and 11 intradermal tests). The highest rate of positive skin tests was observed in the quinolone group, whereas penicillins, carbapenems, tetracyclines, and lincosamides showed the lowest positivity rates. No cross-reactivity between antibiotics was detected. Conclusion: Most antibiotic skin tests in patients with a history of allergy were negative; therefore, a general history of allergy may not be a risk factor for IgE-mediated antibiotic allergy.